Online Public Relations Communication Strategy by Akar Tuli Malang in Campaigning the Use of Indonesian Sign Languange (BISINDO) - Jeffrey Hendrawan; Daniel Budiana; Astri Yogatama (Communication Science Department - Petra Christian University, 2023)
This study aims to determine the online public relations strategy for Akar Tuli Malang Community in campaigning the use of Indonesian sign language (BISINDO). BISINDO is a sign system used by Deaf in Indonesia to communicate. Akar Tuli Malang is the first Deaf community in East Java which is a place for Deaf and hearing friends to socialize. In carrying out its goals, Akar Tuli Malang has a public relations division that carries out the task of establishing cooperation with various parties, both internal and external. The method used in this research is a case study with a qualitative approach and is a type of descriptive research. The results of the study show that the design of a strategy that refers to the concept of a public relations strategy according to Pinkleton has six stages of strategy and the Malang Deaf Root has carried out five of them. Consists of conceptualization, monitoring, planning, organization and coordination, administration and evaluation. In carrying out the strategy online, PR utilizes social media Instagram as a medium for conveying campaign messages.